Trade Relations Between The Khiva Khanate And The British Empire In The 19th Century (The Peerian Journal, 2024)
The trade relations between the Khiva Khanate and the British Empire in the 19th century were shaped by a complex interplay of political, economic, and strategic factors. This article explores the historical context, key events, and the impact of these relations on both entities. The study utilizes primary and secondary sources to analyze the motivations behind British interests in Central Asia, the response of the Khiva Khanate, and the broader implications for regional trade dynamics. The findings reveal that while direct trade was limited, the interactions between the two powers significantly influenced the geopolitics of Central Asia and laid the groundwork for future engagements in the region.